Berberine, an epiphany against cancer - Guaman Ortiz, L. (2017)
Alkaloids are used in traditional medicine for the treatment of many diseases. These compounds are synthesized in plants as secondary metabolites and have multiple effects on cellular metabolism. Among plant derivatives with biological properties, the isoquinoline quaternary alkaloid berberine possesses a broad range of therapeutic uses against several diseases. In recent years, berberine has been reported to inhibit cell proliferation and to be cytotoxic towards cancer cells. Based on this evidence, many derivatives have been synthesized to improve berberine efficiency and selectivity; the results so far obtained on human cancer cell lines support the idea that they could be promising agents for cancer treatment. The main properties of berberine and derivatives will be illustrated.